The Effect of Cash Flow Analysis in Increasing Financial Efficiency of PT Nusantara Medika Utama: Pengaruh Analisis Arus Kas Dalam Peningkatan Efisiensi Keuangan PT Nusantara Medika Utama - Ainia Ayu Silvia; Sugeng Purwanto (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
In an effort to improve the quality of healthcare services, NMU focuses on strengthening capacity and operational efficiency, particularly in response to the surge in demand for digital services post-pandemic. This activity analyzes the impact of cash flow on the financial efficiency of PT Nusantara Medika Utama (NMU) during the 2022-2023 period. The method used is descriptive quantitative, with analysis of secondary data from NMU's financial statements, including the balance sheet, income statement, and cash flow statement. The results of this study show an increase in operational performance indicators, such as the Bed Occupancy Rate (BOR), which rose to 86.99%, and a decrease in Total Liabilities by 15.21%. It can be concluded that effective cash flow management contributes to the improvement of NMU’s financial efficiency. The proposed solutions include a cash flow monitoring system and staff training for better financial management. These findings are expected to contribute to NMU's business sustainability and the improvement of healthcare quality in Indonesia.